The role of medical thoracoscopy in the diagnosis of exudative lymphocytic pleural effusions: an observational study - Pradeep Naik G; Swathi Karanth MP; Aravind Ram; Akshata JS; Raghu BP; Nagaraja C (Monaldi Archives for Chest Disease)
Diagnosis of pleural effusion remains challenging despite extensive microbiological and radiological investigations. Pleural histopathological examination (HPE) is often needed to ascertain the etiology. Medical thoracoscopy (MT) is surpassing the other modalities of pleural biopsy on account of its high diagnostic yield. We aim to estimate the yield of MT in undiagnosed exudative lymphocytic pleural effusion and also intend to correlate gross thoracoscopy findings with HPE results. This retrospective observational study was conducted in a tertiary respiratory care center. Medical records of undiagnosed exudative lymphocytic predominant pleural effusion patients who underwent MT during the study period of 24 months were retrieved from the Medical Records Department. The clinico-demographic profile, radiological images, gross thoracoscopy findings, HPE reports, and post-procedure complications were recorded and analyzed using analysis of variance and chi-square test. The study comprised 62 patients with a mean age of 52 years at presentation. HPE of MT-guided biopsy confirmed tuberculosis in 22 (35.3%), malignancy in 18 (29%) cases, and 22 (35.5%) cases had chronic nonspecific inflammation. The most commonly observed MT finding in malignancy was pleural nodules (14.70%), followed by thickened pleura (10.50%) and growth (2.10%). In tuberculosis, the most common MT finding was adhesions in all, followed by nodules (5.28%). We also diagnosed a case of pleural amoebiasis and ependymoma, which are rare. Macroscopic findings had a significant correlation with the final histopathologic diagnosis, with a diagnostic yield of 66.1%. Gross thoracoscopic findings correlate well with the histopathological diagnosis of pleural effusion etiology, with a correlation coefficient of 0.73. Pleural nodules were the most common finding in malignancy, while adhesions were common in benign pathology like tuberculosis. A good diagnostic yield underscores the utility of MT in undiagnosed exudative lymphocytic pleural effusions.